Pipeline for generating stable large genomic deletions in zebrafish, from small domains to whole gene excisions. Issue 12 (9th September 2021) - Tromp, Alisha; Robinson, Kate; Hall, Thomas E; Mowry, Bryan; Giacomotto, Jean
Abstract: Here we describe a short feasibility study and methodological framework for the production of stable, CRISPR/Cas9-based, large genomic deletions in zebrafish, ranging from several base pairs (bp) to hundreds of kilobases (kb). Using a cocktail of four single guide RNAs (sgRNAs) targeting a single genomic region mixed with a marker-sgRNA against the pigmentation gene tyrosinase, we demonstrate that one can easily and accurately excise genomic regions such as promoters, protein domains, specific exons, or whole genes. We exemplify this technique with a complex gene family, neurexins, composed of three duplicated genes with multiple promoters and intricate splicing processes leading to thousands of isoforms. We precisely deleted small regions such as their transmembrane domains (150 bp deletion in average) to their entire genomic locus (300 kb deletion for nrxn1a for instance). We find that both the concentration and ratio of Cas9/sgRNAs are critical for the successful generation of these large deletions and, interestingly, that in our study, their transmission frequency does not seem to decrease with increasing distance between sgRNA target sites. Considering the growing reports and debate about genetically compensated small indel mutants, the use of large-deletion approaches is likely to be widely adopted in studies of gene function. This strategy will also be key to the study of non-coding genomic regions. Note that we are also describing here a custom method to produce the sgRNAs, which proved to be faster and more robust than the ones traditionally used in the community to date.